Application of SDR base station in network upgrade - Erchao HE; Pengjin GENG; Huili ZHANG (Dianxin kexue)
Based on the unique technical characteristics and existing equipment ability of the SDR base station,and the main problems in deploying SDR base station,faced with the network developing environment and operating conditions for operators,the main application scene of SDR base station was put forward,and the new ideas of using GL1800 to construct light-state network in city and county scene were discussed.